Advances In Furnace Monitoring: Instrumentation - R. MacRosty (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
The demand to increase production levels in smelting furnaces has driven the increase in the power levels. Consequently, greater cooling capacity of the furnace shell has been necessary, resulting in the widespread use of water-cooled elements to protect the refractory linings. Since water ingress into the furnace is an explosion hazard, monitoring and maintenance of the water-cooled elements is of key importance. Some of Hatch's recent research and development efforts have been focused on methods to provide an increased level of monitoring of water-cooled furnace elements; this paper focuses on two technologies developed for this purpose. The first involves the installation of a fibre optic temperature sensor in a water-cooled tapblock. The sensor is capable of providing high accuracy temperature measurements with a fine spatial resolution throughout the tapblock. Hatch has already developed a diagnostic system that uses multivariate statistical analysis to interpret the large quantities of data generated by the sensor. A second technology under development is concerned with enhancing the operating integrity and safety through detection of leaks in the water circuits. A successful leak detection strategy requires minimal maintenance and the ability to detect minute leaks. An instrument that meets these criteria has been investigated and is currently under development. This paper focuses on the technology and results from the test work that has been completed to date.